Analysis of the Nutritional Quality of Local Feed Ingredients Commonly Used in the Concentrate Formula for Beef Cattle Feedlots in Indonesia - Huda, Thoriqul Irfah Al; Agus, Ali; Noviandi, Cuk Tri; Andarwati, Siti; Astuti, Andriyani (Buletin Peternakan, 2024)
Indonesia's annual beef consumption is experiencing a steady rise. In 2021, the per capita beef consumption amounted to 2.56 kg per person per year, resulting in a total of 696 million kilograms consumed across the country. This quantity is equivalent to the slaughtering of approximately 3.98 million cattle annually. With the increasing growth of the feedlot industry, cattle farmers, including feedlot operators, have the opportunity to enhance the value of agricultural companies in Indonesia by utilizing local feedstuffs. The objective of this study was to assess the suitability and nutritional value of indigenous feed sources for beef cattle in Indonesia. The research utilized feedstuff varieties and characteristics sourced from feedlots spanning since 2012-2021. The employed methodologies encompassed surveys, interviews, and questionnaires. This research involved the collection of both primary and secondary data. The potential and quality of local feedstuff were described using descriptive analysis. This research showed that eight types of local feedstuff could be categorized as energy sources including dehydrated cassava chips with a total digestible nutrients (TDN) value of 84.2% and bran pollard with a TDN value of 66.6%. The fiber sources consisted of corn cob (37.7% crude fiber), coffee husk (38% crude fiber), cocoa bean shell (20% crude fiber), tapioca solid waste/onggok (22% crude fiber), and palm kernel meal (22.1% crude fiber). The protein source consisted of copra meal with a protein content of 22.4%. The physical test most frequently inspected the feed color (18.1%) and odor (18.1%). Moisture examination (24%) was the most frequently used of proximate analysis was employed to identify the chemical composition. In conclusion the existence of eight local ingredients which were categorized into three different types: energy source, protein source, and fiber source commonly used in the concentrate formula for beef cattle feedlots in Indonesia.